Isoenergetic replacement of fat by starch in diets for African catfish (Clarias gariepinus): effect on water fluxes in the gastro intestinal tract. - Till S Harter; Johan A J Verreth; Leon T N Heinsbroek; Johan W Schrama (PLoS ONE, 2013)
The effect of an isoenergetic replacement of dietary fat by starch, on chyme characteristics and water fluxes in the gastro intestinal tract (GIT) was assessed. Adult African catfish (Clarias gariepinus) were fed a starch (SD) or fat (FD) diet and groups of fish were dissected at 2, 5 and 8 h after the consumption of a single meal. Chyme was collected quantitatively and was analysed for osmolality and dry matter (DM) content. Postprandial water fluxes were calculated, while using yttrium oxide (Y(2)O(3)) as an inert marker to account for the absorption of DM along the GIT. The largest differences in chyme characteristics between diets were observed in the stomach and decreased towards subsequent compartments. A high initial osmotic pressure was measured in the stomach for both diets (up to 498 ± 2 mOsm kg(-1)) and was likely the driver for the endogeneous water influx to this compartment. Large additions of water were recorded to the stomach and proximal intestine for both diets and absorption of water took place in the mid- and distal intestine. Interestingly, the dietary treatment had an impact on water balance in the stomach and proximal intestine of the fish, but not in the mid- and distal intestine. A strong complementary relationship suggested that 59% of the water fluxes in the proximal intestine could be explained by previous additions to the stomach. Therefore, a higher dietary inclusion of starch led to a shift in water additions from the proximal intestine to the stomach. However, the sum of water additions to the GIT was not different between diets and was on average 6.52 ± 0.85 ml water g(-1) DM. The interactions between osmoregulation and digestion, in the GIT of fed freshwater fish, deserve further attention in future research.